On the Emergence, Current State, and Future Perspectives of Socially Responsible Investment - Puaschunder, Julia (Consilience, 2016)
In recent decades Socially Responsible Investment (SRI) emerged into an en vogue investment philosophy. Originating from religious and moral considerations, SRI evolved in the wake of socio-political deficiencies and corporate social conduct. In the global rise of financial social conscientiousness, differing national legislations and regulatory traditions have led to various SRI practices, which are harmonized by the United Nations (UN). Building on the historic advancement of Financial Social Responsibility in the wake of socio-ethical deficiencies, this paper highlights the future potential of SRI in the aftermath of the 2008/09 World Financial Crisis as a means to avert economic market downfalls. During the current financial market reform, additional micro- and macro-research on financial social conduct could foster the idea of Financial Social Responsibility and aid a successful implementation of SRI.